Mitochondrial dysfunction in Huntington's disease: the bioenergetics of isolated and in situ mitochondria from transgenic mice - Jorge M A Oliveira (2007)
Mitochondrial dysfunction is believed to participate in Huntington's disease (HD) pathogenesis. Here we compare the bioenergetic behavior of forebrain mitochondria isolated from different transgenic HD mice (R6/2, YAC128 and Hdh150 knock-in) and wild-type littermates with the first determination of in situ respiratory parameters in intact HD striatal neurons. We assess the Ca2+-loading capacity of isolated mitochondria by steady Ca2+-infusion. Mitochondria from R6/2 mice (12-13 weeks) and 12 months YAC128, but not homozygous or heterozygous Hdh150 knock-in mice (15-17 weeks), exhibit increased Ca2+-loading capacity when compared with respective wild-type littermates. In situ mitochondria in intact striatal neurons show high respiratory control. Moreover, moderate expression of full-length mutant huntingtin (in Hdh150 knock-in heterozygotes) does not significantly impair mitochondrial respiration in unstimulated neurons. However, when challenged with energy-demanding stimuli (NMDA-receptor activation in pyruvate-based media to accentuate the mitochondria role in Ca2+-handling), Hdh150 neurons are more vulnerable to Ca2+-deregulation than neurons from their wild-type littermates. These results stress the importance of assessing HD mitochondrial function in the cellular context.